Cloud storage services: a study of user satisfaction among public and private sector employees in Klang Valley / Sazlin Ahmad Taufek and Nora'ayu Ahmad Uzir - Ahmad Taufek, Sazlin; Ahmad Uzir, Nora'ayu (Faculty of Information Management, 2022)
In recent years, there has been a significant increase in the number of peoples utilising cloud storage. This has resulted in a significant increase in cloud storage research and development. However, research in user satisfaction is still scarce. This study aims to close this gap by identifying the level of user satisfaction in cloud storage services usage among public and private sectors employees in the Klang Valley, as well as, examining whether perceived ease of use, trust, cost consumption, experience, social influences and security have a significant relationship with user satisfaction. The study used quantitative method, in which there are 205 participants from public and private sector employees who are working around Klang Valley who have responded to the online questionnaires. Then, the data were analyzed by using SPSS 25 and PLSSEM 3.0 to examine the relationship between variables and to test the hypotheses. The finding reveals user satisfaction using cloud storage services among public and private sector employees in Klang Valley and the significant relation between the variables. The benefits obtained from this study can be used to empowered cloud storage services in the public and private sector employees in Klang Valley. Also, it will enhance the quality of services hence advancing the quality of public and private sector of operation of works.